2017
DOI: 10.1016/j.jtcme.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analgesic and anti-inflammatory activity of Bridelia retusa (Spreng) bark

Abstract: Several species of Bridelia have been used in the condition of pain & arthritis in Indian folk medicine. Present study revealed the preliminary phytochemical investigation and evaluation of analgesic, anti-inflammatory and anti-arthritic activity as well as underlying mechanism of bark of Bridelia retusa Spreng. (Euphorbiaceae). The bark was subjected to extraction using pet.ether, ethyl acetate and acetone. All the extracts were significantly inhibit abdominal writhings response and licking time in late phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…Several species of this genus have been used in traditional medicinal systems for the management of multiple diseases, including diabetes, urinary stones, lumbago, rheumatism, venereal diseases, bronchitis, gastrointestinal problems, cardiac pain, infertility, epilepsy, and diarrhoea, among others [9]. Keeping this in view, the biological efficacy of several Bridelia species has been claimed in several research pieces [10][11][12][13][14][15]. In earlier studies, the chemical profiles of the members of the Bridelia genus have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several species of this genus have been used in traditional medicinal systems for the management of multiple diseases, including diabetes, urinary stones, lumbago, rheumatism, venereal diseases, bronchitis, gastrointestinal problems, cardiac pain, infertility, epilepsy, and diarrhoea, among others [9]. Keeping this in view, the biological efficacy of several Bridelia species has been claimed in several research pieces [10][11][12][13][14][15]. In earlier studies, the chemical profiles of the members of the Bridelia genus have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Lupeol acetate identified in Cariniana domestica (Mart.) Miers family Lecythidaceae and Bride-lia retusa (Spreng) family Euphorbiaceae presented anti-inflammatory effect in skin inflammation and in adjuvant-induced arthritis models [28,29]. One of the anti-inflammatory mechanisms of lupeol acetate in arthritis models was the suppression of pro-inflammatory cytokines expression and inhibition of osteoclastogenesis [30].…”
Section: Discussionmentioning
confidence: 99%
“…By intravenously injecting Evans blue, we could monitor the vascular permeability to the site of inflammation [42]. Acetic acid causes peritoneal inflammation and induces an increase in PGE 2 and PGF 2a in the peritoneal fluid [43]. This capillary permeability assay is a typical model for acute phase of inflammation, where mediators of inflammation released following stimulation lead to the dilation of both arterioles and venules and increase capillary permeability [24].…”
Section: Discussionmentioning
confidence: 99%